Diagnostic evaluation of Mathematics for the fourth grade in a Costa Rican private educational institution within the framework of curricular reform - Poveda-Vásquez, Ricardo (2023)
[Objective] The objective of the diagnostic test was to determine the level of progress of an institutional curricular reform during the pandemic and post-pandemic periods to make immediate decisions for the 2022 school year. [Methodology] The type of research is inferential-exploratory, with a quantitative approach. Fifty-one (51) fourth grade students participated. The individual written test consisting of 19 items, was applied simultaneously in November 2021 for 60 minutes. Its preparation was based on teachers’ opinions and propositions. The Classical Test Theory (CTT) was used to interpret the results and SPSS 28.0.1.0 and its programming language, as well as the R environment were used. [Results] Analysis of the test results produced a Cronbach’s alpha value of 0.79, with three very difficult items and one very easy item. The grades that were located in the first quartile were subjected to a personalized analysis. The mathematical areas in which the test takers displayed the greatest mastery were Measurement, and Statistics and Probability, while they showed the least mastery of Geometry. For the second problem involving the development of a solution, almost 14% of the students obtained a perfect score and 40% did not obtain any points. [Conclusions] In the area of Numbers it was clear that the presentation of abbreviated multiplication should be strengthened. In the case of Geometry, it was determined that students were too dependent on memorization, while in the area of Relations and Algebra, results showed that it was necessary to vary the type of sequences used. In Statistics and Probability, it was observed that students can read information from a graph. Finally, it was determined that Problem Solving should be emphasized more in the classroom to guarantee better results in the development of solutions.